A novel sensitive scandium-plumbagin complex: Characterization and fluorescence spectrophotometric application for scandium determination in ceramic samples - Do Tam Nhan (Elsevier B.V., 2025)
Scandium (Sc), a rare earth element, has increasingly been used in various fields such as aerospace, electronics and advanced materials. Accurate and highly sensitive Sc analysis is very important in practice. However, existing analytical methods are often limited in sensitivity, selectivity or require complex equipment. In this paper, a new complex of Sc(III) and plumbagin was studied. The optimal conditions were established: λex =500 nm and λem =600 nm, optimal pH from 5.5 to 6.5, acetonitrile:water ratio of 1:3 (V/V), and most of the metal ions were unaffected and stable at room temperature. Based on UV–Vis, fluorescence, FT-IR, 1H NMR, 13C NMR, ESI-MS, XPS, and quantum calculations, it was confirmed that the complex had a ratio of 1:2 (Sc:PLB) with a stability constant of 5.06 ×106 M2; on that basis, the complex structure was proposed. For development and validation, the values of method detection limit (MDL), limit of quantification (LOQ), relative standard deviation (RSD), recovery, and repeatability (RSDR) were determined as 0.06 ppm, 0.18 ppm, 0.34 %, 99.4 % 100.5 %, and 0.52–1.11 %, respectively. Those values confirmed that it can be applied for analytical purposes. The pro posed method has high selectivity and sensitivity, requires simple equipment, and simplicity, was successfully applied to analyze Sc in ancient glacial ceramics, providing valuable insights into their provenance and manufacturing techniques. The analytical results were consistent when compared with those obtained by neutron activation analysis (NAA), affirming the accuracy and reliability of the proposed method. This research provides a promising and practical method for Sc analysis, contributing to advances in analytical chemistry and related fields.